At Untimely Crossroads of the Real and the Unreal - MNATSAKANYAN, DIANA (Bulletin of Yerevan University B: Philology, 2021)
In the following article, some elements typical to postmodern life-perception such as temporal violation and absence of border between the real and the unreal manifestation of the independence period Armenian poetry are observed. While observing itbecomes clear that poetry of 90’s characterized by postmodernism’s chaos and uncertainty and poem’s hero, as a rule, is situated between the real and the imagined in the closed maze, where the only period of time is permanent present. Due to the mentioned above postmodern ideology’s features typical, which are partly caused by those year’s reality, the works make strong emotive impression making the reader think endlessly.
Keywords: postmodernism, non-differentiation between reality and imagination, choice of a new hero, loneliness, maze, time circle, permanent present, seeming movement